2017
DOI: 10.1142/s0192415x17500203
|View full text |Cite
|
Sign up to set email alerts
|

Antitumor and Immunomodulatory Effect ofGastrodia elataon Colon CancerIn VitroandIn Vivo

Abstract: Gastrodia elata Blume (GE) is a well-known kind of herb that has been used in traditional medicine for thousands of years. The extrusion of raw materials from it could improve flavor and enhance bioavailability in food and drug development. The purpose of this study is to investigate antitumor and immune boosting effects of extruded GE in human colon carcinoma cells, splenocytes, and mice-bearing CT26 colon carcinoma cell. Treatment with 100[Formula: see text][Formula: see text]g/mL of extruded GE decreased ce… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
7
0

Year Published

2017
2017
2025
2025

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 17 publications
(7 citation statements)
references
References 24 publications
0
7
0
Order By: Relevance
“…These compounds have been received increasing interest due to their potential biological properties such as anti-tumor, anti-oxidant, and anti-inflammatory actions [12131415]. Additionally, with their high attention, many researchers have demonstrated potential neuroprotective properties of vanillin and 4-HBA against neuronal injury using in vitro and in vivo experiments.…”
Section: Introductionmentioning
confidence: 99%
“…These compounds have been received increasing interest due to their potential biological properties such as anti-tumor, anti-oxidant, and anti-inflammatory actions [12131415]. Additionally, with their high attention, many researchers have demonstrated potential neuroprotective properties of vanillin and 4-HBA against neuronal injury using in vitro and in vivo experiments.…”
Section: Introductionmentioning
confidence: 99%
“…Experiments proved that Chinese herbal medicine and its extracts can inhibit the growth of tumor cells or prevent the occurrence and development of tumors in various ways. TCM, such as Rhizoma Dioscorea, [26] Rhizoma Arisaematis, [27] Bombyx Batryticatus, [28] Coptis Chinensis, [29] Fructus Lycii, [30,31] Cyathula Officinalis, [32] Astragalus Membranaceus, [33][34][35] Phellodenron Amurense, [36] Cornus officinalis, [37] Gastrodiiae Elata, [38] Ziziphus Jujuba, [39] Polygala Tenuifolia, [40] and Eclipta Prostrata [41] have been confirmed the effect of antitumor. Berberine, the extract of Rhizoma Coptidis, can directly induce apoptosis.…”
Section: Discussionmentioning
confidence: 99%
“…Gastrodia elata (GE) Blume is a belong to the to the Orchidaceae family and used for treating nervous diseases such as headaches, migraine, dizziness, and epilepsy (Matias et al, 2016;Zhan et al, 2016). A number of studies have shown that GE possess a variety of pharmacological activities including antiinflammatory, analgesic, anti-oxidative, memory-improving and anti-aging, anti-virus and anti-tumor activities (Zhan et al, 2016, Kim et al, 2017. However, there has been no precise information on whether GE regulates intestinal inflammation.…”
Section: Original Articlementioning
confidence: 99%